Israel’s security concern of Arab uprisings - Abdallah Asmer,; Zarina Othman,; Ravichandran Moorthy, (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2019)
The regional security of the Middle East has been changed since the so called Arab Spring started in late 2010. This paper seeks to study the Israeli strategic situation in the changing regional security of the Middle East since the Arab Uprisings incepted. The research questions focused on the main concerns for Israel since the Arab Uprisings incepted and the response of Israel. Israel looked to the uprisings as a strategic change which could affect its security. Even though Israel seems more stable while other regional powers were affected by conflicts, Israel has been faced new challenges in fragile region. The main security challenges emerged for Israel were the liquidity of the region for ambiguous future, the rise of the non-state armed groups within the region and the emerging influence of Iran in the region. Israel relied on its strategic relations with the US and other super powers and its strategic military superiority in the region to deal with the situation. It worked as well on developing its relations with the moderate Arab states like Egypt and Saudi Arabia in face of Iran.